Doctors’ knowledge, practices, challenges, and limitations regarding disclosure of bad news: A multicentre study from Pakistan - Asma Usman; Sameena Shah; Samar Zaki; Kashmira Nanji; Sobiya Sawani; Saher Naseeb Uneeb; Naseem Bari; Obaid Ullah; Sumera Abid (Journal of Family Medicine and Primary Care)
Background: Breaking bad news is one of the most difficult tasks for practicing doctors, especially for those working in health care specialties where life-threatening diseases are diagnosed and managed routinely. Our aim was to elicit the knowledge and practices of doctors and identify barriers faced by them in disclosure of bad news across the provinces of Pakistan. Methods: Cross-sectional, multi-centered study supported by an external grant in 15 Government and Private Hospitals across Pakistan. A total of 1185 doctors were surveyed. Responses were compared across provinces. Results: 80% of doctors across all specialties considered life-threatening diagnoses like cancer and stroke as equivalent to bad news, whereas less than 50% perceived conditions like malaria and typhoid as bad news. Regarding the level of difficulty encountered in giving bad news on a scale of 0 to 6, over 57% doctors rated it 4 and above. The reasons identified were lack of confidentiality, lack of privacy, lack of time, lack of training, fear of patients’ and family reactions, not wanting to hurt the patient or causing more distress, concern of having failed the patient, and their own reactions among others. Conclusions: Technical proficiency, training, good patient-centered communication, and incorporating socio-cultural aspects are essential for effective disclosure of bad news.